Automated Quantification of Subcellular Particles in Myogenic Progenitors. Issue 12 (8th December 2021) - Filippelli, Romina L.; Omer, Amr; Li, Shulei; van Oostende‐Triplet, Chloë; Gallouzi, Imed E.; Chang, Natasha C.
Abstract: Fluorescence microscopy is a powerful tool enabling the visualization of protein localization within cells. In this article, we outline an automated and non‐biased way to detect and quantify subcellular particles using immunocytochemistry, fluorescence microscopy, and the program CellProfiler. We discuss the examination of two types of subcellular particles: messenger ribonucleoprotein (mRNP) granules, namely processing bodies and stress granules, and autophagosomes. Fluorescent microscopy Z‐stacks are acquired and deconvolved, and maximum intensity images are generated. The number of subcellular particles per cell is then quantified using the described CellProfiler pipeline. We also explain how to isolate primary myoblast progenitor cells from mice, which were used to obtain the presented results. Last, we discuss the critical parameters to be considered for each of these techniques. Both mRNP granules and autophagosomes play important roles in sequestering intracellular cargo, such as messenger RNAs and RNA‐binding proteins for mRNP granules and cytoplasmic waste for autophagosomes. The methods outlined in this article are widely applicable for studies relating to subcellular particle formation, localization, and flux during homeostasis, following stimuli, and during disease. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Immunofluorescence microscopy of messenger ribonucleoprotein granules in primary myoblasts Alternate Protocol : Immunofluorescence microscopy of autophagosomes in primary myoblasts Support Protocol : Isolation of primary myoblasts from mice Basic Protocol 2 : Automated quantification of subcellular particles